The Ongoing U.S. Struggle with Maternal Mortality - O'Brien, James A.; Lewkowitz, Adam K.; Main, Elliot K.; Adashi, Eli Y. (American Journal of Perinatology, 2024)
Despite significant efforts over the past two decades, the maternal mortality rate (MMR) in the United States remains at least double that of most other high-income countries (HICs). In addition, substantial racial disparities exist with MMRs among Black and American Indian/Alaska Native women two to three times higher than White, Hispanic, and Asian/Pacific Islander counterparts. Of the three surveillance systems currently in place, Maternal Mortality Review Committees (MMRCs) are widely considered to provide the highest quality data. MMRCs in combination with Perinatal Quality Collaboratives and other successful initiatives provide the best hope of reversing these concerning trends. The state of maternal health in the United States is at a critical juncture. To reach the ultimate goal of rendering the United States as one of the “safest countries in the world to give birth” will require greater coordination and consolidation of national efforts across the entire prenatal, perinatal, and postpartum continuum. The authors make suggestions to create a robust federal infrastructure to finally provide equitable high-quality maternal care and bring U.S. maternal mortality into alignment with other HICs.
Keywords: maternal mortality; maternal morbidity; health equity; international comparators